PERAN PENDIDIKAN DALAM PERKEMBANGAN KEAGAMAAN ANAK BERKEBUTUHAN KHUSUS - Muchlisin, Imam; Habibi, Rohim (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
Education is the right for every Indonesian citizen, without exception. However, there are still many children with special needs in Indonesia who have not gained decent access to education. This is a serious concern, considering that every child has the right to get an education that suits their needs and potential. This study aims to describe the concepts and implementation of individual education programs at SLB Budi Mulya Jepon. This research is a qualitative-field research with a phenomenological approach. Data collection methods using in -depth observations, participatory interviews, and documentation. Data analysis is descriptive. Research data sources include organizers, educators, education staff, and parents of students. The results showed that schools have core values ​​that underlie all activities in the implementation of education, namely diniyah, amaliyah, ukhuwah, and ilmiyah. In developing religious behavior of children with special needs, the school applies several programs including religious habituation activities, such as memorization of the Qur'an, prayer in congregation, reading of prayers, and pilgrimage founder of ponpok pesantren, and the application of individual education programs through routine Koran activities by the teacher companion and parents